NASAB ANAK DISKA SEBAB HAMIL DALAM PANDANGAN ULAMA DAN PENCATATAN ADMINISTRASI KEPENDUDUKANNYA DI INDONESIA - Hakim, Zainul; Dahlan, Moh.; Siraj, A. Malthuf (International Conference on Humanity Education and Society (ICHES), 2024)
The pheneomenon of sexual intercourse outside the marriage is officially acknowledged by underage marriage dispensation granted by the court which is given based on an urgent reason that the applicant has been pregnant eventhough she is under age. After the court has given this dispensation copy to KUA (Local Religious Affairs Office), it is officially admitted that the child of the couple is an adultery child who is legally problematic for his/her family lineage and mahram. In fiqh, the nasab of children of adultery could be determined by reffering to the perpsective stated by jumhuru al-fuqaha' group and mu'ashirah fatwa. However, the procedure for recording the adultery children's identity contradicts to the Islamic law. Therefore, the focus of this research was: (1) how was the view of the ulama in determining the family lineage of adultery children? (2) Who was responsible for overseeing the legal administration records of adultery children in Indonesia? This research applied normative juridical method.